Thickening agent composition, thickening agent as well as preparation method and application of thickening agent

By using a polymer combination of hydrazide structure and carbonyl structure, a thickener with dynamic covalent bonds is formed, which solves the problem of insufficient performance of solid-phase drilling fluid in high-temperature and high-salt environments, and achieves a significant improvement in shear force, meeting the development needs of high-temperature and low-pressure oil and gas reservoirs.

CN119799293APending Publication Date: 2025-04-11CHINA NAT PETROLEUM CORP +1

Patent Information

Application Number
CN202311306848.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing solid-phase drilling fluids have poor filtration loss loss, easy leakage, and insufficient temperature resistance in high-temperature and high-salt environments, which are difficult to meet the efficient development needs of high-temperature and low-pressure oil and gas reservoirs.

Method used

A combined thickener with a hydrazide structure and a polymer B with a carbonyl structure is used to form a network structure in the solution through acylzone-type dynamic covalent bonds, thereby improving the temperature and salt resistance of the solid-phase water-based drilling fluid.

Benefits of technology

It significantly improves the shear force of solid-phase water-based drilling fluid, enhances its stability and performance under high-temperature and high-salt conditions, and meets the efficient development needs of high-temperature and low-pressure oil and gas reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004486492160000041
    Figure BDA0004486492160000041
  • Figure BDA0004486492160000071
    Figure BDA0004486492160000071
  • Figure BDA0004486492160000101
    Figure BDA0004486492160000101
Patent Text Reader

Abstract

The invention relates to the technical field of oilfield chemistry, and discloses a thickening agent composition, a thickening agent as well as a preparation method and application of the thickening agent. The thickening agent composition contains a polymer A having a hydrazide structure and a polymer B having a carbonyl structure, wherein the polymer A has a structural unit derived from a first nonionic monomer, a structural unit derived from a first anionic monomer, and a structural unit derived from a hydrazide group-containing monomer; and a polymer B having a structural unit derived from a second nonionic monomer, a structural unit derived from a second anionic monomer, and a structural unit derived from a carbonyl group-containing monomer. According to the thickening agent disclosed by the invention, the thickening agent has excellent temperature resistance and salt resistance, and the shearing force of the solid-free water-based drilling fluid can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a thickener composition, a thickener, and a preparation method and application thereof. Background Art

[0002] As the drilling depth of oil and gas wells continues to increase, the geological conditions during the drilling process become more complex. The high temperature, high pressure, and high-salt formation environment make it difficult to control the performance of drilling fluids, which puts higher requirements on drilling fluid technology. During the drilling process, the solid phase particles of various treatment agents such as bentonite, temporary plugging agents, weighting agents, and plugging agents in the drilling fluid invade the reservoir under the action of the pressure difference between the liquid column pressure of the wellbore working fluid and the formation pore pressure, blocking the pores and roaring channels, causing reservoir damage, which is not conducive to the efficient development of oil and gas fields in the later stage. Solid-free drilling fluid is a drilling fluid that does not contain solid phases such as bentonite and barite, and uses polymers and soluble salts as the main additives. It is one of the current main reservoir protection drilling fluids. Since solid-free drilling fluids do not contain active bentonite, it is impossible to rely on the ability of bentonite particles to provide the basic viscosity-enhancing and shear-enhancing ability of the drilling fluid through the space network. Therefore, the role of polymers as flow type regulators is very important. In addition, since the solid-free drilling fluid does not contain barite for weighting, its density can only be controlled by the type and concentration of dissolved inorganic salts, which places higher requirements on the salt resistance and interaction capabilities of polymer molecules.

[0003] At present, the use of bentonite-free or solid-free water-based drilling fluid systems in production layers usually has technical difficulties such as poor filtration reduction and easy leakage. In addition, the system's temperature resistance is poor, which is far from meeting the needs of developing high-temperature and low-pressure oil and gas reservoirs, seriously restricting the efficient development of high-temperature and low-pressure oil and gas reservoirs.

[0004] CN114805678A discloses a drilling fluid thickener and a preparation method thereof, wherein the preparation method is as follows: unsaturated amino acid ester and halogenated alkane are subjected to quaternization reaction to obtain a long-chain hydrophobic monomer; the long-chain hydrophobic monomer, acrylamide, acrylic acid, sulfonic acid monomer, surfactant, deionized water, pH regulator and initiator are subjected to polymerization reaction to obtain the drilling fluid thickener. The obtained polymer can be used for thickening of non-solid phase drilling fluid, and has a certain effect in saturated NaCl solution before and after aging.

[0005] CN115772243A discloses a thickener for solid-free drilling fluid and its preparation method and application, which utilizes the electrostatic interaction between salt ions in formate brine and functional groups on the thickener molecular chain to form a reversible and stable three-dimensional network structure, significantly improving the temperature resistance and calcium resistance of the polymer. The preparation method of the thickener is as follows: acrylamide, sulfonate monomer, quaternary ammonium salt monomer, alkyl substituted acrylamide, alkyl substituted tertiary amine monomer, copolymerize under the action of redox or azo initiators to obtain a thickener for solid-free drilling fluid. The obtained polymer has a good thickening effect in drilling fluid weighted by potassium formate.

[0006] CN111704695A discloses a multifunctional drilling treatment agent and its preparation and application. By effectively combining the comprehensive effects of natural macromolecules and synthetic polymers, the product's cutting performance is achieved, and the suspension and sand carrying capacity of the drilling fluid are improved. The preparation method of the treatment agent is as follows: starch, cellulose, acrylamide, a water-soluble compound monomer containing a double bond, an oxidant, a reducing agent, an alcohol solvent and a dispersing stabilizer are reacted to obtain a multifunctional drilling treatment agent. The obtained polymer can be used for viscosity enhancement and cutting improvement of solid-free drilling fluid, and can withstand aging at 120°C.

[0007] The above patents all achieve the viscosity-enhancing and shear-improving properties of polymers by grafting natural polymers or utilizing the hydrophobic association, electrostatic and other effects between synthetic polymers. In this process, the following deficiencies often exist: the temperature resistance of the modified natural polymer products is poor and it is difficult to be applied to working conditions at temperatures of 150°C and above; the molecular rigidity of acrylamide synthetic polymers is insufficient and they tend to form entanglements in the solution and mainly produce a viscosity-enhancing effect; the salt resistance of synthetic polymers is poor and it is difficult to be applied to divalent salts (Ca 2+ Mg 2+) working conditions with very high concentration; the strength of hydrophobic association, electrostatic and other effects is weak, and it is difficult to improve the sufficient intermolecular network structure strength at high temperature. Since the 21st century, oil exploration and development has been developed in the direction of oceans, complex formations, deep wells, medium-deep wells and ultra-deep wells, which puts forward higher requirements for drilling fluid treatment agents. Practice has proved that due to the limitations of the performance of traditional thickeners, they can no longer meet the more stringent requirements of actual application conditions. In recent years, measures to improve the temperature and salt resistance of acrylamide polymers have mainly focused on their molecular modification, introducing functional groups with different structures and characteristics into their molecules, and improving their performance by changing the intramolecular or intermolecular effects of polymers. Some progress has been made, but how to further improve the performance of polymers so that they can better adapt to the needs of complex formations is currently lacking in the corresponding basic theoretical support, which makes the improvement of temperature-resistant polymers lack theoretical guidance and has a large degree of blindness. Therefore, studying the relationship between the structure of temperature-resistant polymers and solution characteristics, providing basic theories for improving polymer performance, and developing efficient temperature-resistant polymer thickeners have become one of the problems that need to be solved urgently. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems of thickeners in the prior art and to provide a temperature-resistant and calcium-resistant solid-free drilling fluid and completion fluid thickener composition, a thickener and a preparation method and application thereof. The thickener of the present invention has excellent temperature resistance and salt resistance and can significantly improve the shear force of the solid-free water-based drilling fluid.

[0009] The inventors of the present invention have found through in-depth research that the thickener combination of the present invention contains a polymer A with a hydrazide structure and a polymer B with a carbonyl structure. When the two polymers are mixed in a solution, a thickener for solid-free water-based drilling fluid can be obtained by utilizing the characteristics of forming an acylhydrazone type dynamic covalent bond between the hydrazide structure and the carbonyl structure. The thickener dissolves rapidly, has excellent temperature and salt resistance, and can significantly improve the shear force of the solid-free water-based drilling fluid, thereby completing the present invention.

[0010] Therefore, the present invention provides a thickener composition in one aspect, wherein the thickener composition contains a polymer A having a hydrazide structure and a polymer B having a carbonyl structure,

[0011] The polymer A has a structural unit derived from a first nonionic monomer, a structural unit derived from a first anionic monomer, and a structural unit derived from a hydrazide group-containing monomer;

[0012] The polymer B has a structural unit derived from a second nonionic monomer, a structural unit derived from a second anionic monomer, and a structural unit derived from a carbonyl group-containing monomer.

[0013] Preferably, the polymer A has 5-90% by mass of a structural unit derived from a first nonionic monomer, 5-90% by mass of a structural unit derived from a first anionic monomer, and 1-45% by mass of a structural unit derived from a hydrazide group-containing monomer.

[0014] Preferably, the polymer B has 4.5-86% by mass of structural units derived from the second nonionic monomer, 4.5-86% by mass of structural units derived from the second anionic monomer, and 4.5-50% by mass of structural units derived from the carbonyl group-containing monomer.

[0015] Preferably, the mass ratio of the polymer A to the polymer B is 1:(0.2-5).

[0016] Preferably, the polymer A further comprises a structural unit derived from a first crosslinking agent.

[0017] Preferably, the first cross-linking agent is selected from one or more of triallylamine, tetraallylammonium chloride, tetraallylammonium bromide, tetraallylethylenediamine, tetraallylpropylenediamine and tetraallylbutylenediamine.

[0018] Preferably, the polymer B further has a structural unit derived from a second crosslinking agent.

[0019] Preferably, the second cross-linking agent is one or more compounds of the following structure:

[0020]

[0021] In the formula, R1 and R2 are H or allyl, and at least one of them is allyl; R3 and R4 are H or allyl, and at least one of them is allyl; R5 is allyl; m is 1-10, and n is 0-5.

[0022] Preferably, the first nonionic monomer is selected from one or more of N-hydroxymethyl acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide, N-n-butyl acrylamide, acryloyl morpholine, vinyl pyrrolidone and vinyl caprolactam.

[0023] Preferably, the first anionic monomer is one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate and sodium methyl propylene sulfonate.

[0024] Preferably, the hydrazide group-containing monomer is selected from one or more of methacrylic hydrazide, ethylacrylic hydrazide, acrylhydrazide, crotonylhydrazide, crotonyldiazide, pentylhydrazide and hexylhydrazide.

[0025] Preferably, the second nonionic monomer is selected from one or more of N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, acryloylmorpholine and vinylpyrrolidone.

[0026] Preferably, the second anionic monomer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate and sodium vinyl sulfonate.

[0027] Preferably, the carbonyl-containing monomer is selected from one or more of diacetone acrylamide, 4-pentene-2-one, 4-methyl-4-pentene-2-one, 5-hexene-2-one and 5-methyl-5-hexene-2-one.

[0028] Preferably, the composition also contains water.

[0029] Preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(10-500).

[0030] Preferably, the water is brine, and the salt in the brine is selected from one or more of calcium chloride, calcium bromide, sodium chloride, sodium bromide, sodium formate, potassium formate and cesium formate.

[0031] Preferably, the density of the brine is 1.15-2.3 g / cm 3 Salt water based drilling fluid.

[0032] According to a second aspect of the present invention, a method for preparing a thickener is provided, wherein the method comprises the following steps:

[0033] 1) in the presence of a first solvent, a first crosslinking agent and an initiator, a first nonionic monomer, a first anionic monomer and a hydrazide group-containing monomer are subjected to a first polymerization reaction to obtain a polymer A having a hydrazide structure;

[0034] 2) in the presence of a second solvent, a second crosslinking agent, an initiator, a reducing agent and an oxidizing agent, subjecting a second nonionic monomer, a second anionic monomer and a carbonyl-containing monomer to a second polymerization reaction to obtain a polymer B having a carbonyl structure;

[0035] 3) A step of mixing the polymer A, the polymer B and water.

[0036] Preferably, in step 1), the mass ratio of the first nonionic monomer to the first anionic monomer is 1:(0.1-10).

[0037] Preferably, the ratio of the total mass of the first nonionic monomer and the first anionic monomer to the mass of the hydrazide group-containing monomer is 1:(0.01-0.8).

[0038] Preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer and the hydrazide group-containing monomer to the mass of the first cross-linking agent is 1:(0.0005-0.1).

[0039] Preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer, the hydrazide group-containing monomer and the first cross-linking agent to the mass of the first solvent is 1:(1-60).

[0040] Preferably, the mass ratio of the first solvent to the first initiator is 1:(0.0001-0.01).

[0041] Preferably, the first nonionic monomer is selected from one or more of N-hydroxymethyl acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide, N-n-butyl acrylamide, acryloyl morpholine, vinyl pyrrolidone and vinyl caprolactam.

[0042] Preferably, the first anionic monomer is one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate and sodium methyl propylene sulfonate.

[0043] Preferably, the hydrazide group-containing monomer is selected from one or more of methacrylic hydrazide, ethylacrylic hydrazide, acrylhydrazide, crotonylhydrazide, crotonyldiazide, pentylhydrazide and hexylhydrazide.

[0044] Preferably, the first cross-linking agent is selected from one or more of triallylamine, tetraallylammonium chloride, tetraallylammonium bromide, tetraallylethylenediamine, tetraallylpropylenediamine and tetraallylbutylenediamine.

[0045] Preferably, the first initiator is an azo initiator.

[0046] Preferably, the first initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, azobisisopropylimidazoline hydrochloride and azobiscyanovaleric acid.

[0047] Preferably, the first solvent is a mixed solvent of an alcohol compound and water, and the alcohol compound is one or more of methanol, ethanol, n-propanol, isopropanol, isobutanol and tert-butanol.

[0048] Preferably, the mass ratio of the alcohol compound to water is (0.1-10):1.

[0049] Preferably, the conditions of the first polymerization reaction include: pH 6-11, reaction temperature 25-70° C., and reaction time 1-10 h.

[0050] Preferably, the mass ratio of the second nonionic monomer to the second anionic monomer is 1:(0.1-10).

[0051] Preferably, the ratio of the total mass of the second nonionic monomer and the second anionic monomer to the mass of the carbonyl-containing monomer is 1:(0.05-1).

[0052] Preferably, the ratio of the total mass of the second nonionic monomer, the second anionic monomer and the carbonyl-containing monomer to the mass of the second crosslinking agent is 1:(0.00005-0.002).

[0053] Preferably, the ratio of the total mass of the second nonionic monomer, the second anionic monomer, the carbonyl-containing monomer and the second crosslinking agent to the mass of the second solvent is 1:(0.5-20).

[0054] Preferably, the reducing agent contains a first reducing agent and a second reducing agent, the oxidizing agent contains a first oxidizing agent and a second oxidizing agent, and the mass ratio of the second solvent, the first reducing agent, the second reducing agent, the second initiator, the first oxidizing agent, and the second oxidizing agent is 1:(0.000001-0.0001):(0.00001-0.0002):(0.00002-0.0005):(0.00001-0.0003):(0.000001-0.00005).

[0055] Preferably, the second nonionic monomer is selected from one or more of N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, acryloylmorpholine and vinylpyrrolidone.

[0056] Preferably, the second anionic monomer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate and sodium vinyl sulfonate.

[0057] Preferably, the carbonyl-containing monomer is selected from one or more of diacetone acrylamide, 4-pentene-2-one, 4-methyl-4-pentene-2-one, 5-hexene-2-one and 5-methyl-5-hexene-2-one.

[0058] Preferably, the second cross-linking agent is one or more compounds of the following structure:

[0059]

[0060] In the formula, R1 and R2 are H or allyl, and at least one of them is allyl; R3 and R4 are H or allyl, and at least one of them is allyl; R5 is allyl; m is 1-10, and n is 0-5.

[0061] Preferably, the second initiator is an azo initiator.

[0062] Preferably, the second initiator is one or more of azobisisobutylamidine hydrochloride, azobisisopropylimidazoline hydrochloride and azobiscyanovaleric acid.

[0063] Preferably, the first reducing agent is one or more of ferrous sulfate, ferrous ammonium sulfate, ferrous chloride and ferrous ammonium chloride.

[0064] Preferably, the second reducing agent is one or more of sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium dithionite and sodium formaldehyde sulfoxylate.

[0065] Preferably, the second oxidant is one or more of potassium persulfate, sodium persulfate and ammonium persulfate.

[0066] Preferably, the second oxidant is hydrogen peroxide and / or dibenzoyl peroxide.

[0067] Preferably, the conditions of the second polymerization reaction include: pH 6.5-8, initial reaction temperature -2-8°C, and reaction time 1-5h.

[0068] Preferably, in step 3), the mass ratio of the polymer A to the polymer B is 1:(0.8-2.5).

[0069] Preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(15-200).

[0070] Preferably, the water is saline.

[0071] According to a third aspect of the present invention, a thickener is provided, comprising the thickener composition according to the first aspect of the present invention and water.

[0072] According to a fourth aspect of the present invention, there is provided a thickener obtained by mixing the components of the thickener composition according to the first aspect of the present invention.

[0073] According to the fifth aspect of the present invention, there is provided a use of the thickener composition described in the first aspect of the present invention, the thickener described in the third aspect of the present invention or the thickener described in the fourth aspect of the present invention in the preparation of temperature-resistant and calcium-resistant solid-free drilling fluid and completion fluid.

[0074] Through the above technical scheme, a temperature-resistant and calcium-resistant solid-free drilling fluid and completion fluid thickener composition, a thickener and its preparation method and application can be provided. The thickener of the present invention has excellent temperature resistance and salt resistance, and can significantly improve the shear force of the solid-free water-based drilling fluid. DETAILED DESCRIPTION

[0075] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0076] According to a first aspect of the present invention, a thickener composition is provided, wherein the thickener composition comprises a polymer A having a hydrazide structure and a polymer B having a carbonyl structure,

[0077] The polymer A has a structural unit derived from a first nonionic monomer, a structural unit derived from a first anionic monomer, and a structural unit derived from a hydrazide group-containing monomer;

[0078] The polymer B has a structural unit derived from a second nonionic monomer, a structural unit derived from a second anionic monomer, and a structural unit derived from a carbonyl group-containing monomer.

[0079] According to the present invention, in order to further improve the temperature and salt resistance, and thus further improve the shear force of the solid-free water-based drilling fluid, preferably, the polymer A has 5-90% by mass of structural units derived from the first non-ionic monomer, 5-90% by mass of structural units derived from the first anionic monomer, and 1-45% by mass of structural units derived from a hydrazide group-containing monomer; more preferably, the polymer A has 5-70% by mass of structural units derived from the first non-ionic monomer, 20-90% by mass of structural units derived from the first anionic monomer, and 3-30% by mass of structural units derived from a hydrazide group-containing monomer.

[0080] According to the present invention, in order to further improve the temperature and salt resistance, and thus further improve the shear force of the solid-free water-based drilling fluid, preferably, the polymer B has 4.5-86% by mass of structural units from the second non-ionic monomer, 4.5-86% by mass of structural units from the second anionic monomer and 4.5-50% by mass of structural units from the carbonyl-containing monomer; more preferably, the polymer B has 5-60% by mass of structural units from the second non-ionic monomer, 15-60% by mass of structural units from the second anionic monomer and 5-40% by mass of structural units from the carbonyl-containing monomer.

[0081] In the present invention, the content of the structural unit is calculated based on the ratio of monomer feed.

[0082] According to the present invention, for the purpose of constructing a network structure between polymer molecules and improving the viscosity-increasing and shear-enhancing properties of the system, preferably, the mass ratio of the polymer A to the polymer B is 1:(0.2-5); more preferably, the mass ratio of the polymer A to the polymer B is 1:(0.8-2.5).

[0083] According to the present invention, preferably, the polymer A also has a structural unit derived from a first crosslinking agent. By having a structural unit derived from the first crosslinking agent, the polymer A can have a high degree of branching, thereby improving the temperature resistance, salt resistance, and crosslinking properties of the polymer.

[0084] Preferably, the first cross-linking agent is selected from one or more of triallylamine, tetraallylammonium chloride, tetraallylammonium bromide, tetraallylethylenediamine, tetraallylpropylenediamine and tetraallylbutylenediamine.

[0085] According to the present invention, preferably, in the polymer A, the content of the structural unit derived from the first cross-linking agent may be 0.05-10% by mass, preferably 0.2-6% by mass.

[0086] According to the present invention, preferably, the polymer B further comprises a structural unit derived from a second cross-linking agent. By comprising a structural unit derived from a second cross-linking agent, the polymer can have a multi-branched structure, thereby enhancing the rigidity of the polymer molecules in the solution.

[0087] According to the present invention, preferably, the second cross-linking agent is one or more compounds of the following formula:

[0088]

[0089] In the formula, R1 and R2 are H or allyl, and at least one of them is allyl; R3 and R4 are H or allyl, and at least one of them is allyl; R5 is allyl; m is 1-10, and n is 0-5.

[0090] By using the second cross-linking agent of the above structure, the advantages of enhancing the viscosity, shear strength, temperature and salt resistance of the polymer B are improved.

[0091] According to the present invention, preferably, in the polymer B, the content of the structural unit derived from the second cross-linking agent may be 0.005-0.2% by mass, preferably 0.02-0.15% by mass.

[0092] According to the present invention, the first nonionic monomer may be various nonionic monomers commonly used in the art. Preferably, the first nonionic monomer is selected from one or more of N-methylol acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide, N-n-butyl acrylamide, acryloyl morpholine, vinyl pyrrolidone and vinyl caprolactam; more preferably, the first nonionic monomer is selected from one or more of N-methylol acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide and N-n-butyl acrylamide; particularly preferably, the first nonionic monomer is selected from N,N-dimethyl acrylamide.

[0093] According to the present invention, the first anionic monomer may be various anionic monomers commonly used in the art. Preferably, the first anionic monomer is one or more of 2-acrylamide-2-methylpropane sulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate and sodium methyl propylene sulfonate; more preferably, the first anionic monomer is 2-acrylamide-2-methylpropane sulfonic acid.

[0094] According to the present invention, preferably, the hydrazide group-containing monomer is selected from one or more of methacrylic hydrazide, ethylacrylic hydrazide, acrylhydrazide, crotonylhydrazide, crotonylhydrazide, pentylhydrazide and hexylhydrazide; more preferably, the hydrazide group-containing monomer is selected from one or more of methacrylic hydrazide, ethylacrylic hydrazide and acrylhydrazide; particularly preferably, the hydrazide group-containing monomer is acrylhydrazide.

[0095] According to the present invention, the second nonionic monomer can also be various nonionic monomers commonly used in the art. Preferably, the second nonionic monomer is selected from one or more of N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, acryloylmorpholine and vinylpyrrolidone; more preferably, the second nonionic monomer is selected from one or more of N-ethylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide; particularly preferably, the first nonionic monomer is selected from N,N-dimethylacrylamide.

[0096] According to the present invention, the second anionic monomer can be various anionic monomers commonly used in the art. Preferably, the second anionic monomer is selected from one or more of 2-acrylamide-2-methylpropane sulfonic acid, sodium styrene sulfonate and sodium vinyl sulfonate; more preferably, the second anionic monomer is 2-acrylamide-2-methylpropane sulfonic acid.

[0097] According to the present invention, preferably, the carbonyl-containing monomer is selected from one or more of diacetone acrylamide, 4-pentene-2-one, 4-methyl-4-pentene-2-one, 5-hexene-2-one and 5-methyl-5-hexene-2-one; more preferably, the carbonyl-containing monomer is diacetone acrylamide.

[0098] According to the present invention, preferably, the composition further contains water. Preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(10-500); more preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(15-200).

[0099] According to the present invention, preferably, the water is salt water, and the salt water may be salt water adjusted with soluble salts to different densities until saturation.

[0100] Preferably, the salt used as the brine is selected from one or more of calcium chloride, calcium bromide, sodium chloride, sodium bromide, sodium formate, potassium formate and cesium formate.

[0101] In addition, the density of the brine is preferably 1.15-2.3 g / cm 3 .

[0102] In the present invention, the polymer A and the polymer B are both made of monomers with excellent solubility and resistance to high temperature hydrolysis as raw materials, and both have a certain branched structure, so they can be used in a water-based drilling fluid system weighted by calcium salt.

[0103] According to a second aspect of the present invention, a method for preparing a thickener is provided, wherein the method comprises the following steps:

[0104] 1) in the presence of a first solvent, a first crosslinking agent and an initiator, a first nonionic monomer, a first anionic monomer and a hydrazide group-containing monomer are subjected to a first polymerization reaction to obtain a polymer A having a hydrazide structure;

[0105] 2) in the presence of a second solvent, a second crosslinking agent, an initiator, a reducing agent and an oxidizing agent, subjecting a second nonionic monomer, a second anionic monomer and a carbonyl-containing monomer to a second polymerization reaction to obtain a polymer B having a carbonyl structure;

[0106] 3) A step of mixing the polymer A, the polymer B and water.

[0107] According to the present invention, preferably, in step 1), the mass ratio of the first nonionic monomer to the first anionic monomer is 1:(0.1-10); more preferably, the mass ratio of the first nonionic monomer to the first anionic monomer is 1:(1-10); further preferably, the mass ratio of the first nonionic monomer to the first anionic monomer is 1:(2-6).

[0108] The first nonionic monomer and the first anionic monomer are as described above and are not described in detail herein.

[0109] According to the present invention, preferably, in step 1), the ratio of the total mass of the first nonionic monomer and the first anionic monomer to the mass of the monomer containing a hydrazide group is 1:(0.01-0.8); more preferably, the ratio of the total mass of the first nonionic monomer and the first anionic monomer to the mass of the monomer containing a hydrazide group is 1:(0.03-0.45); further preferably, the ratio of the total mass of the first nonionic monomer and the first anionic monomer to the mass of the monomer containing a hydrazide group is 1:(0.05-0.2).

[0110] The hydrazide group-containing monomer is as described above and will not be described in detail here.

[0111] According to the present invention, preferably, in step 1), the ratio of the total mass of the first nonionic monomer, the first anionic monomer and the monomer containing a hydrazide group to the mass of the first cross-linking agent is 1:(0.0005-0.1); more preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer and the monomer containing a hydrazide group to the mass of the first cross-linking agent is 1:(0.001-0.05); further preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer and the monomer containing a hydrazide group to the mass of the first cross-linking agent is 1:(0.005-0.02).

[0112] The first cross-linking agent is as described above and will not be described in detail here.

[0113] According to the present invention, preferably, in step 1), the ratio of the total mass of the first nonionic monomer, the first anionic monomer, the monomer containing a hydrazide group and the first cross-linking agent to the mass of the first solvent is 1:(1-60); more preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer, the monomer containing a hydrazide group and the first cross-linking agent to the mass of the first solvent is 1:(1.1-22).

[0114] Preferably, the first solvent can be one or more of an alcohol compound and water; more preferably, the first solvent is a mixed solvent of an alcohol compound and water. In addition, the mass ratio of the alcohol compound to water is (0.1-10):1, preferably (0.1-5):1.

[0115] Examples of the alcohol compound include one or more of methanol, ethanol, n-propanol, isopropanol, isobutanol and tert-butanol.

[0116] In a particularly preferred embodiment of the present invention, the first solvent is a mixed solvent of an alcohol compound and water, and the ratio of the total mass of the first nonionic monomer, the first anionic monomer, the hydrazide group-containing monomer and the first cross-linking agent to the mass of the alcohol compound and the mass of water is 1:(0.1-10):(1-50), more preferably 1:(0.1-7):(1-15).

[0117] In the present invention, the polymerization activity of the monomer containing a hydrazide group is relatively poor, but by controlling the molecular weight and solubility of the polymer through copolymerization in an alcohol / water system under the action of the first cross-linking agent, a rigid molecular product with a high degree of branching can be obtained, thereby improving the temperature resistance, salt resistance and cross-linking properties of the polymer.

[0118] According to the present invention, preferably, in step 1), the mass ratio of the first solvent to the first initiator is 1:(0.0001-0.01); more preferably, the mass ratio of the first solvent to the first initiator is 1:(0.0002-0.008).

[0119] The first initiator is preferably an azo initiator, more preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, azobisisopropylimidazoline hydrochloride and azobiscyanovaleric acid.

[0120] According to the present invention, preferably, in step 1), the conditions of the first polymerization reaction include: pH 6-11, reaction temperature 25-70°C, reaction time 1-10h; more preferably, the conditions of the first polymerization reaction include: pH 6-9, reaction temperature 35-65°C, reaction time 2-6h.

[0121] According to the present invention, preferably, in step 2), the mass ratio of the second nonionic monomer to the second anionic monomer is 1:(0.1-10); more preferably, the mass ratio of the second nonionic monomer to the second anionic monomer is 1:(0.1-3); further preferably, the mass ratio of the second nonionic monomer to the second anionic monomer is 1:(0.5-3).

[0122] The second nonionic monomer and the second anionic monomer are as described above and are not described in detail herein.

[0123] According to the present invention, preferably, in step 2), the ratio of the total mass of the second nonionic monomer and the second anionic monomer to the mass of the carbonyl-containing monomer is 1:(0.05-1); more preferably, in step 2), the ratio of the total mass of the second nonionic monomer and the second anionic monomer to the mass of the carbonyl-containing monomer is 1:(0.05-0.6); further preferably, in step 2), the ratio of the total mass of the second nonionic monomer and the second anionic monomer to the mass of the carbonyl-containing monomer is 1:(0.1-0.4).

[0124] The carbonyl-containing monomer is as described above and will not be described in detail here.

[0125] According to the present invention, preferably, in step 2), the ratio of the total mass of the second nonionic monomer, the second anionic monomer and the carbonyl-containing monomer to the mass of the second cross-linking agent is 1:(0.00005-0.002); more preferably, in step 2), the ratio of the total mass of the second nonionic monomer, the second anionic monomer and the carbonyl-containing monomer to the mass of the second cross-linking agent is 1:(0.0001-0.001); further preferably, in step 2), the ratio of the total mass of the second nonionic monomer, the second anionic monomer and the carbonyl-containing monomer to the mass of the second cross-linking agent is 1:(0.0001-0.0006).

[0126] The second cross-linking agent is as described above and will not be described in detail here.

[0127] According to the present invention, preferably, in step 2), the ratio of the total mass of the second nonionic monomer, the second anionic monomer, the carbonyl-containing monomer and the second cross-linking agent to the mass of the second solvent is 1:(0.5-20); preferably, in step 2), the ratio of the total mass of the second nonionic monomer, the second anionic monomer, the carbonyl-containing monomer and the second cross-linking agent to the mass of the second solvent is 1:(1-10).

[0128] Preferably, the second solvent is one or more of water, formamide and dimethylformamide; more preferably, the second solvent is water.

[0129] According to the present invention, preferably, the reducing agent contains a first reducing agent and a second reducing agent, the oxidizing agent contains a first oxidizing agent and a second oxidizing agent, and the mass ratio of the second solvent, the first reducing agent, the second reducing agent, the second initiator, the first oxidizing agent, and the second oxidizing agent is 1:(0.000001-0.0001):(0.00001-0.0002):(0.00002-0.0005):(0.00001-0.0003):(0.000001-0.00005 ); More preferably, the reducing agent contains a first reducing agent and a second reducing agent, the oxidizing agent contains a first oxidizing agent and a second oxidizing agent, and the mass ratio of the second solvent, the first reducing agent, the second reducing agent, the second initiator, the first oxidizing agent, and the second oxidizing agent is 1:(0.000005-0.00006):(0.00002-0.00012):(0.00005-0.0005):(0.00003-0.0002):(0.000005-0.00003).

[0130] Preferably, the second initiator is an azo initiator; more preferably, the second initiator is one or more of azobisisobutylamidine hydrochloride, azobisisopropylimidazoline hydrochloride and azobiscyanovaleric acid; particularly preferably, the second initiator is azobisisobutylamidine hydrochloride.

[0131] Preferably, the first reducing agent is one or more of ferrous sulfate, ammonium ferrous sulfate, ferrous chloride and ammonium ferrous chloride; more preferably, the first reducing agent is ferrous sulfate.

[0132] Preferably, the second reducing agent is one or more of sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium dithionite and sodium formaldehyde sulfoxylate; more preferably, the second reducing agent is sodium sulfite.

[0133] Preferably, the second oxidant is one or more of potassium persulfate, sodium persulfate and ammonium persulfate; more preferably, the second oxidant is potassium persulfate.

[0134] Preferably, the second oxidant is hydrogen peroxide and / or dibenzoyl peroxide; more preferably, the second oxidant is hydrogen peroxide.

[0135] In step 2) of the present invention, a three-stage initiation system of low temperature, medium temperature and high temperature is used to reduce the reaction temperature, thereby increasing the molecular weight of the product and ensuring that the system temperature does not rise too high due to polymerization exotherm, thereby avoiding thermal crosslinking in the later stage of polymerization. The molecular weight of the product is further increased under the action of the second crosslinking agent, thereby preparing a high molecular weight product with a weakly branched structure and improving the viscosity-increasing and crosslinking properties of the polymer.

[0136] According to the present invention, preferably, in step 2), the conditions of the second polymerization reaction include: pH 6-11, initial reaction temperature 6-11, reaction time 1-10h; more preferably, the conditions of the second polymerization reaction include: pH 6.5-8, initial reaction temperature -2-8°C, reaction time 1-5h.

[0137] According to the present invention, preferably, in step 3), the mass ratio of the polymer A to the polymer B is 1:(0.2-5); more preferably, the mass ratio of the polymer A to the polymer B is 1:(0.8-2.5); further preferably, the mass ratio of the polymer A to the polymer B is 1:(1-2).

[0138] According to the present invention, preferably, in step 3), preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(10-500); more preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(15-200).

[0139] According to the present invention, preferably, the water is salt water, and the salt water may be salt water adjusted with soluble salts to different densities until saturation.

[0140] Preferably, the salt used as the brine is selected from one or more of calcium chloride, calcium bromide, sodium chloride, sodium bromide, sodium formate, potassium formate and cesium formate.

[0141] In addition, the density of the brine is preferably 1.15-2.3 g / cm 3 .

[0142] According to a third aspect of the present invention, a thickener is provided, comprising the thickener composition according to the first aspect of the present invention and water.

[0143] Preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(10-500); more preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(15-200).

[0144] According to the present invention, preferably, the water is salt water, and the salt water may be salt water adjusted with soluble salts to different densities until saturation.

[0145] Preferably, the salt used as the brine is selected from one or more of calcium chloride, calcium bromide, sodium chloride, sodium bromide, sodium formate, potassium formate and cesium formate.

[0146] In addition, the density of the brine is preferably 1.15-2.3 g / cm 3 .

[0147] According to a fourth aspect of the present invention, there is provided a thickener obtained by mixing the components of the thickener composition according to the first aspect of the present invention.

[0148] According to a fifth aspect of the present invention, there is provided a use of the thickener composition or thickener of the present invention in preparing temperature-resistant and calcium-resistant solid-free drilling fluid and completion fluid.

[0149] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0150] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0151] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0152] Example 1

[0153] (1) Preparation of polymers containing hydrazide structures

[0154] 10 g of N,N-dimethylacrylamide, 30 g of 2-acrylamido-2-methylpropanesulfonic acid, 4 g of acrylhydrazide, 0.3 g of tetraallylethylenediamine, 0.5 g of azobisisobutyronitrile, 60 g of isopropanol, and 400 g of deionized water were added to a three-necked glass bottle equipped with a stirrer, a nitrogen tube, and a thermometer. After stirring until all the raw materials were dissolved, nitrogen was introduced for 30 min, the pH was controlled at 7.8, the temperature was controlled at 50° C., and then azobisisobutylamidine hydrochloride was added. The reaction was carried out for 5 h. The product was dried and crushed to obtain a polymer containing a hydrazide structure.

[0155] (2) Preparation of polymers containing carbonyl structures

[0156] 10 g of N,N-dimethylacrylamide, 15 g of 2-acrylamido-2-methylpropanesulfonic acid, 5 g of diacetone acrylamide, 0.008 g of crosslinker-2 (m is 2.6, n is 1.1), and 150 g of deionized water are added to a three-necked glass bottle equipped with a stirrer, a nitrogen tube, and a thermometer, and stirred until all the raw materials are dissolved, and then nitrogen is introduced for 30 min, the pH is controlled at 7.5, the temperature is controlled at 0°C, and then 0.003 g of ferrous sulfate, 0.01 g of sodium sulfite, 0.025 g of azobisisobutylamidine hydrochloride, 0.015 g of potassium persulfate, and 0.002 g of hydrogen peroxide are added, and the reaction is carried out for 4 h, and then the temperature is increased to 60°C, and the reaction is carried out for 1 h, and the product is dried and crushed to obtain a polymer containing a carbonyl structure;

[0157] (3) Preparation of thickener

[0158] 5 g of polymer containing hydrazide structure and 8 g of polymer containing carbonyl structure were added into 600 g of brine (density 1.28 g / cm 3 Calcium chloride salt water), stir and dissolve to obtain a thickening agent.

[0159] Example 2

[0160] The method of Example 1 is followed, except that in step (1), nonionic monomer-1 is 7 g N,N-diethylacrylamide and 3 g vinyl pyrrolidone.

[0161] Example 3

[0162] The method of Example 1 was followed, except that in step (1), anionic monomer-1 was 25 g of 2-acrylamido-2-methylpropanesulfonic acid and 15 g of sodium vinyl sulfonate.

[0163] Example 4

[0164] The method of Example 1 is followed, except that in step (1), the hydrazide-containing monomer is methacryloyl hydrazide, and the added amount is 8 g.

[0165] Example 5

[0166] The method of Example 1 was followed, except that in step (1), the crosslinking agent-1 was triallylamine, and the added amount was 0.6 g.

[0167] Example 6

[0168] The method of Example 1 was followed, except that in step (1), the azo initiator-1 was azobisisobutylamidine hydrochloride, and the added amount was 0.7 g.

[0169] Example 7

[0170] The method of Example 1 is followed, except that in step (1), the alcohol compound is tert-butyl alcohol, and the amount added is 120 g.

[0171] Example 8

[0172] The method of Example 1 was followed, except that in step (1), the amount of deionized water added was 250 g.

[0173] Example 9

[0174] The method of Example 1 was followed, except that in step (1), the reaction pH was controlled at 8.5, the temperature was controlled at 55° C., and the time was controlled at 3.5 h.

[0175] Example 10

[0176] The method of Example 1 is followed, except that in step (2), nonionic monomer-2 is 10 g N,N-dimethylacrylamide, 8 g acryloylmorpholine and 2 g vinyl pyrrolidone.

[0177] Embodiment 11

[0178] The method of Example 1 is followed, except that in step (2), anionic monomer-2 is 20 g of 2-acrylamido-2-methylpropanesulfonic acid and 5 g of sodium styrenesulfonate.

[0179] Example 12

[0180] The method of Example 1 was followed, except that in step (2), the amount of diacetone acrylamide added was 10 g.

[0181] Embodiment 13

[0182] The method of Example 1 was followed, except that in step (2), the amount of diacetone acrylamide added was 3 g.

[0183] Embodiment 14

[0184] The method of Example 1 was followed, except that in step (2), m in cross-linking agent-2 was 3.2, n was 0.3, and the added amount was 0.01 g.

[0185] Embodiment 15

[0186] The method of Example 1 was followed, except that in step (2), m in cross-linking agent-2 was 5.5, n was 0.7, and the added amount was 0.005 g.

[0187] Example 16

[0188] The method of Example 1 was followed, except that in step (2), the amount of deionized water added was 250 g.

[0189] Embodiment 17

[0190] The method of Example 1 was followed, except that in step (2), the reducing agent-1 was ammonium ferrous sulfate, added in an amount of 0.0015 g; the reducing agent-2 was sodium thiosulfate, added in an amount of 0.012 g; the azo initiator-2 was azobiscyanovaleric acid, added in an amount of 0.04 g; the oxidizing agent-1 was sodium persulfate, added in an amount of 0.011 g; and the oxidizing agent-2 was dibenzoyl peroxide, added in an amount of 0.0025 g.

[0191] Embodiment 18

[0192] The method of Example 1 was followed, except that in step (2), the reducing agent-1 was ferrous chloride, added in an amount of 0.0045 g; the reducing agent-2 was sodium dithionite, added in an amount of 0.009 g; the azo initiator-2 was azobiscyanovaleric acid, added in an amount of 0.015 g; the oxidizing agent-1 was ammonium persulfate, added in an amount of 0.002 g; and the oxidizing agent-2 was hydrogen peroxide, added in an amount of 0.001 g.

[0193] Embodiment 19

[0194] The method of Example 1 was followed, except that in step (2), the reaction pH was controlled at 7.3, the initial reaction temperature was controlled at -1°C, and the reaction was continued for 3 h.

[0195] Embodiment 20

[0196] The method of Example 1 was followed, except that in step (2), the reaction pH was controlled at 6.8, the initial reaction temperature was controlled at 6°C, and the reaction was carried out for 2.5 hours.

[0197] Embodiment 21

[0198] The method of Example 1 is followed, except that in step (3), the amount of the polymer containing a carbonyl structure added is 5 g.

[0199] Embodiment 22

[0200] The method of Example 1 is followed, except that in step (3), the amount of the polymer containing a carbonyl structure added is 11 g.

[0201] Embodiment 23

[0202] The method of Example 1 was followed, except that in step (3), the amount of brine added was 350 g.

[0203] Embodiment 24

[0204] The method of Example 1 was followed, except that in step (3), the amount of brine added was 850 g.

[0205] Embodiment 25

[0206] The method of Example 1 is followed, except that in step (1), acrylhydrazide is replaced by an equal weight of crotonylhydrazide.

[0207] Embodiment 26

[0208] The method of Example 1 is followed, except that in step (1), acrylhydrazide is replaced by pentylhydrazide of the same weight.

[0209] Embodiment 27

[0210] The method of Example 1 is followed, except that in step (1), acrylhydrazide is replaced by an equal weight of methacrylic hydrazide.

[0211] Embodiment 28

[0212] The method of Example 1 is followed, except that in step (2), diacetone acrylamide is replaced with an equal weight of 4-penten-2-one.

[0213] Embodiment 29

[0214] The method of Example 1 is followed, except that in step (2), diacetone acrylamide is replaced with an equal weight of 4-methyl-4-penten-2-one.

[0215] Embodiment 30

[0216] The method of Example 1 is followed, except that in step (2), diacetone acrylamide is replaced with an equal weight of 5-hexen-2-one.

[0217] Embodiment 31

[0218] The method of Example 1 is followed, except that in step (2), diacetone acrylamide is replaced with an equal weight of 5-methyl-5-hexen-2-one.

[0219] Comparative Example 1

[0220] The method of Example 1 was followed, except that acrylhydrazide was not used.

[0221] Comparative Example 2

[0222] The method of Example 1 was followed, except that diacetone acrylamide was not used.

[0223] Test Example 1

[0224] Performance Evaluation

[0225] The brine used in the experiment was a 30% CaCl2 aqueous solution, and 0.5% thiourea was added as a deoxidizer during the system preparation process. The rheological properties of the system were tested, and then it was placed in an aging tank. After aging for 7 days at 150°C, the rheological properties were tested again. The rheological properties were determined according to the method specified in the national standard GB / T 16783.1-2014, and the test temperature was 50°C. The test data are shown in Table 1.

[0226] Table 1

[0227]

[0228] Note: 1-31 is the test data of the thickener obtained in Example 1-31; 32-33 is the test data of the thickener obtained in Comparative Example 1-2.

[0229] As can be seen from Table 1, the thickener for drilling fluid and completion fluid prepared by the present invention has the characteristics of low plastic viscosity (PV), high dynamic shear force (YP), suitable initial shear and final shear under high calcium conditions, and exhibits outstanding rheological and thixotropic properties, which can provide good support for the dynamic carrying of cuttings and static suspension of solid phases of the system. In addition, the system has excellent temperature resistance and can still provide good rheological and thixotropic properties after aging.

[0230] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A thickener composition, characterized in that: The thickener composition contains a polymer A having a hydrazide structure and a polymer B having a carbonyl structure. The polymer A has a structural unit derived from a first nonionic monomer, a structural unit derived from a first anionic monomer, and a structural unit derived from a hydrazide group-containing monomer; The polymer B has a structural unit derived from a second nonionic monomer, a structural unit derived from a second anionic monomer, and a structural unit derived from a carbonyl group-containing monomer.

2. The composition according to claim 1, wherein The polymer A has 5-90% by mass of structural units derived from a first nonionic monomer, 5-90% by mass of structural units derived from a first anionic monomer, and 1-45% by mass of structural units derived from a hydrazide group-containing monomer; Preferably, the polymer B has 4.5-86% by mass of structural units derived from the second nonionic monomer, 4.5-86% by mass of structural units derived from the second anionic monomer, and 4.5-50% by mass of structural units derived from the carbonyl group-containing monomer.

3. The composition according to claim 1, wherein The mass ratio of the polymer A to the polymer B is 1:(0.2-5).

4. The composition according to any one of claims 1 to 3, wherein The polymer A also has a structural unit derived from a first cross-linking agent; Preferably, the first cross-linking agent is selected from one or more of triallylamine, tetraallylammonium chloride, tetraallylammonium bromide, tetraallylethylenediamine, tetraallylpropylenediamine and tetraallylbutylenediamine.

5. The composition according to any one of claims 1 to 3, wherein The polymer B also has a structural unit derived from a second cross-linking agent; Preferably, the second cross-linking agent is one or more compounds of the following formula: In the formula, R1 and R2 are H or allyl, and at least one of them is allyl; R3 and R4 are H or allyl, and at least one of them is allyl; R5 is allyl; m is 1-10, and n is 0-5.

6. The composition according to any one of claims 1 to 3, wherein The first nonionic monomer is selected from one or more of N-hydroxymethyl acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide, N-n-butyl acrylamide, acryloyl morpholine, vinyl pyrrolidone and vinyl caprolactam; Preferably, the first anionic monomer is one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate and sodium methyl propylene sulfonate; Preferably, the hydrazide group-containing monomer is selected from one or more of methacrylic hydrazide, ethylacrylic hydrazide, acrylhydrazide, crotonylhydrazide, crotonyldiazide, pentylhydrazide and hexylhydrazide.

7. The composition according to any one of claims 1 to 3, wherein The second nonionic monomer is selected from one or more of N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, acryloylmorpholine and vinylpyrrolidone; Preferably, the second anionic monomer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate and sodium vinyl sulfonate; Preferably, the carbonyl-containing monomer is selected from one or more of diacetone acrylamide, 4-pentene-2-one, 4-methyl-4-pentene-2-one, 5-hexene-2-one and 5-methyl-5-hexene-2-one.

8. The composition according to any one of claims 1 to 7, wherein The composition also contains water; Preferably, the mass ratio of the total mass of the polymer A and the polymer B to the mass of the water is 1:(10-500); Preferably, the water is salt water, and the salt in the salt water is selected from one or more of calcium chloride, calcium bromide, sodium chloride, sodium bromide, sodium formate, potassium formate and cesium formate; Preferably, the density of the brine is 1.15-2.3 g / cm 3 Salt water based drilling fluid.

9. A method for preparing a thickener, characterized in that: The Method The following steps are included: 1) in the presence of a first solvent, a first crosslinking agent and an initiator, a first nonionic monomer, a first anionic monomer and a hydrazide group-containing monomer are subjected to a first polymerization reaction to obtain a polymer A having a hydrazide structure; 2) in the presence of a second solvent, a second crosslinking agent, an initiator, a reducing agent and an oxidizing agent, subjecting a second nonionic monomer, a second anionic monomer and a carbonyl-containing monomer to a second polymerization reaction to obtain a polymer B having a carbonyl structure; 3) A step of mixing the polymer A, the polymer B and water.

10. The method according to claim 9, wherein: In step 1), the mass ratio of the first nonionic monomer to the first anionic monomer is 1:(0.1-10); Preferably, the ratio of the total mass of the first nonionic monomer and the first anionic monomer to the mass of the hydrazide group-containing monomer is 1:(0.01-0.8); Preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer and the hydrazide group-containing monomer to the mass of the first crosslinking agent is 1:(0.0005-0.1); Preferably, the ratio of the total mass of the first nonionic monomer, the first anionic monomer, the hydrazide-containing monomer and the first crosslinking agent to the mass of the first solvent is 1:(1-60); Preferably, the mass ratio of the first solvent to the first initiator is 1:(0.0001-0.01).

11. The method according to claim 10, wherein: The first nonionic monomer is selected from one or more of N-hydroxymethyl acrylamide, N-ethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide, N-n-butyl acrylamide, acryloyl morpholine, vinyl pyrrolidone and vinyl caprolactam; Preferably, the first anionic monomer is one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate and sodium methyl propylene sulfonate; Preferably, the hydrazide group-containing monomer is selected from one or more of methacrylic hydrazide, ethylacrylic hydrazide, acrylhydrazide, crotonylhydrazide, crotonylhydrazide, pentylhydrazide and hexylhydrazide; Preferably, the first cross-linking agent is selected from one or more of triallylamine, tetraallylammonium chloride, tetraallylammonium bromide, tetraallylethylenediamine, tetraallylpropylenediamine and tetraallylbutylenediamine; Preferably, the first initiator is an azo initiator; Preferably, the first initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, azobisisopropylimidazoline hydrochloride and azobiscyanovaleric acid; Preferably, the first solvent is a mixed solvent of an alcohol compound and water, and the alcohol compound is one or more of methanol, ethanol, n-propanol, isopropanol, isobutanol and tert-butanol; Preferably, the mass ratio of the alcohol compound to water is (0.1-10):

1.

12. The method according to any one of claims 9 to 11, wherein: The conditions of the first polymerization reaction include: pH 6-11, reaction temperature 25-70° C., and reaction time 1-10 h.

13. The method according to any one of claims 9 to 11, wherein: The mass ratio of the second nonionic monomer to the second anionic monomer is 1:(0.1-10); Preferably, the ratio of the total mass of the second nonionic monomer and the second anionic monomer to the mass of the carbonyl-containing monomer is 1:(0.05-1); Preferably, the ratio of the total mass of the second nonionic monomer, the second anionic monomer and the carbonyl-containing monomer to the mass of the second crosslinking agent is 1:(0.00005-0.002); Preferably, the ratio of the total mass of the second nonionic monomer, the second anionic monomer, the carbonyl-containing monomer and the second crosslinking agent to the mass of the second solvent is 1:(0.5-20); Preferably, the reducing agent contains a first reducing agent and a second reducing agent, the oxidizing agent contains a first oxidizing agent and a second oxidizing agent, and the mass ratio of the second solvent, the first reducing agent, the second reducing agent, the second initiator, the first oxidizing agent, and the second oxidizing agent is 1:(0.000001-0.0001):(0.00001-0.0002):(0.00002-0.0005):(0.00001-0.0003):(0.000001-0.00005).

14. The method according to claim 13, wherein: The second nonionic monomer is selected from one or more of N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, acryloylmorpholine and vinylpyrrolidone; Preferably, the second anionic monomer is selected from one or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate and sodium vinyl sulfonate; Preferably, the carbonyl-containing monomer is selected from one or more of diacetone acrylamide, 4-pentene-2-one, 4-methyl-4-pentene-2-one, 5-hexene-2-one and 5-methyl-5-hexene-2-one; Preferably, the second cross-linking agent is one or more compounds of the following formula: In the formula, R1 and R2 are H or allyl, and at least one of them is allyl; R3 and R4 are H or allyl, and at least one of them is allyl; R5 is allyl; m is 1-10, and n is 0-5; Preferably, the second initiator is an azo initiator; Preferably, the second initiator is one or more of azobisisobutylamidine hydrochloride, azobisisopropylimidazoline hydrochloride and azobiscyanovaleric acid; Preferably, the first reducing agent is one or more of ferrous sulfate, ferrous ammonium sulfate, ferrous chloride and ferrous ammonium chloride; Preferably, the second reducing agent is one or more of sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium dithionite and sodium formaldehyde sulfoxylate; Preferably, the second oxidant is one or more of potassium persulfate, sodium persulfate and ammonium persulfate; Preferably, the second oxidizing agent is hydrogen peroxide and / or dibenzoyl peroxide.

15. The method according to claim 13, wherein: The conditions of the second polymerization reaction include: pH 6.5-8, initial reaction temperature -2-8°C, and reaction time 1-5h.

16. The method according to any one of claims 9 to 11, wherein: In step 3), the mass ratio of the polymer A to the polymer B is 1:(0.8-2.5); Preferably, the mass ratio of the total mass of the polymer A and the polymer B to the water is 1:(15-200); Preferably, the water is saline.

17. A thickener comprising the thickener composition according to any one of claims 1 to 7 and water.

18. A thickener obtained by mixing the components of the thickener composition according to any one of claims 1 to 8.

19. Use of the thickener composition according to any one of claims 1 to 7, the thickener according to claim 17 or the thickener according to claim 18 in the preparation of temperature-resistant and calcium-resistant solid-free drilling fluid and completion fluid.

Citation Information

Patent Citations

  • Multifunctional drilling treatment agent and preparation and application thereof

    CN111704695A

Cited By

  • PH-responsive low-temperature gel temporary plugging agent and preparation method thereof

    CN120118665A